What can stimulus polarity and interphase gap tell us about auditory nerve function in cochlear-implant recipients? - Hughes, Michelle L.; Choi, Sangsook; Glickman, Erin (Hearing research, 2018)
Modeling studies suggest that differences in neural responses between polarities might reflect underlying neural health. Specifically, large differences in electrically evoked compound action potential (eCAP) amplitudes and amplitude-growth-function (AGF) slopes between polarities might reflect poorer peripheral neural health, whereas more similar eCAP responses between polarities might reflect better neural health. The interphase gap (IPG) has also been shown to relate to neural survival in animal studies. Specifically, healthy neurons exhibit larger eCAP amplitudes, lower thresholds, and steeper AGF slopes for increasing IPGs. In ears with poorer neural survival, these changes in neural responses are generally less apparent with increasing IPG. The primary goal of this study was to examine the combined effects of stimulus polarity and IPG within and across subjects to determine whether both measures represent similar underlying mechanisms related to neural health. With the exception of one measure in one group of subjects, results showed that polarity and IPG effects were generally not correlated in a systematic or predictable way. This suggests that these two effects might represent somewhat different aspects of neural health, such as differences in site of excitation versus integrative membrane characteristics, for example. Overall, the results from this study suggest that the underlying mechanisms that contribute to polarity and IPG effects in human CI recipients might be difficult to determine from animal models that do not exhibit the same anatomy, variance in etiology, electrode placement, and duration of deafness as humans. •Stimulus polarity primarily has supra-threshold effects on the eCAP.•Anodic-leading pulses yield larger amplitudes and steeper slopes than cathodic.•Longer interphase gaps yield lower thresholds and larger amplitudes.•Interphase gap and polarity effects are generally not correlated.